Marble and Glass Waste Powder in Cement Mortar - Mamaru Yenesew Alemu; Mitiku Damtie Yehualaw; Wallelign Mulugeta Nebiyu; Mulu Derbie Nebebe; Woubishet Zewdu Taffese (Applied Sciences)
The growing demand for cement in construction contributes significantly to environmental degradation due to its high energy consumption and carbon emissions. As a result, there is a pressing need for sustainable alternatives to reduce the environmental footprint of cement production. This study explores the use of marble and glass waste powders as supplementary cementitious materials in mortar production to reduce the environmental impact of cement. By partially replacing cement with varying percentages (0–30%) of marble and glass waste powders, the research evaluates their effects on workability, mechanical properties (compressive strength, density, ultrasonic pulse velocity), and durability (sulfate attack, water absorption, porosity). The results show that a 10% replacement of cement with marble and glass waste powder (MGWP) enhances compressive strength by 25.6% at 28 days and 17.26% at 56 days while improving microstructure and durability through compacted morphology and secondary C-S-H formation. The findings suggest that using MGWP up to 10% is optimal for enhancing the performance of mortar, providing a sustainable alternative to traditional cement with practical implications for greener construction practices.